Exploration of students' computational thinking skills in solving fractional number problems judging from learning style - Sukowati, Berliani Ardelia; Masduki, Masduki (Universitas Islam Negeri Raden Intan Lampung, 2024)
Computational thinking skills play an important role in the 21st century in helping students solve mathematical problems. One of the problem-solving abilities of students is influenced by learning style. The purpose of this study is to explore students' computational thinking skills through visual (V), auditory (A), and kinesthetic (K) learning styles. This research uses a qualitative approach with a case study design. This study uses data collection instruments such as test questions, learning-style questionnaires, and interviews. Before being used, the test questions were validated by two mathematics education experts and tested on five grade V students. Using the test results and the learning style questionnaires, the researcher selected three visual students, one auditory student, and two kinesthetic students. Based on the findings of the research, learning style does not affect students' computational thinking capacity. Students with visual, auditory, and kinesthetic learning styles can meet all indicators of computational thinking: abstraction, pattern recognition, algorithmic thinking, and generalization.